APPLICATION OF DEA METHOD IN ANALYSE OF THE EFFECTIVENESS OF AIR POLLUTION PREVENTION ACTIVITIES - A REGIONAL LEVEL STUDY - Mesjasz-Lech, Agata (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
The article analyses the effectiveness of air quality protection undertakings seen as an element in the assessment of activities aiming at a sustainable development of a country in terms of environmental governance. Environmental governance pertains to the use of natural recourses and the actions reducing the environmental impact of economic activities. Polish provinces are compared on the basis of environmental governance indexes of sustainable development connected with air protection. The analysis uses the DEA method and the following measures serve as variables: 1. determining DEA results:- particulates retained and neutralized in cleaning devices, - sulphur dioxide retained and neutralized in cleaning devices, - nitrogen oxides retained and neutralized in cleaning devices, - carbon oxide retained and neutralized in cleaning devices, 2. determining DEA input: - plants of significant nuisance to air quality with particulate pollutant reduction systems, - plants of significant nuisance to air quality with gaseous pollutant reduction systems, - outlays on fixed assets for protection of air and climate. The year 2012 is the subject of the analysis.